Restricted antibody formation to sheep erythrocytes of allogeneic bone marrow chimeras histoincompatible at the K end of the H-2 complex (The Rockefeller University Press, 1981)
Employing a new method for allogeneic bone marrow transplantation, irradiation chimeras constructed from various combinations of marrow cells from B10 H-2 recombinant mice and AKR recipients were prepared. Though these chimeras had well-developed populations of T and B cells, they showed strikingly different patterns of responses in the primary antibody formation to sheep erythrocytes (SRBC), a T dependent antigen. These are (a) AKR mice treated with C57BL/10 cells, [B10 leads to AKR] fully H-2 incompatible, and AKR mice treated with B10.A (5R) cells, [5R leads to AKR] I-J,E compatible chimeras that were almost completely unresponsive to SRBC; (b) AKR mice treated with B10.BR cells [BR leads to AKR] fully H-2 compatible, and AKR mice treated with B10 AKM cells, [AKM leads to AKR] chimeras where donor and recipient differed only at H-2D, showed the same number of plaque-forming cells (PFC) as B10 control mice; (c) AKR mice treated with B10.A cells, [B10 leads to AKR] chimeras, where donor and recipient were matched at H-2K-I-E region, showed about one-half the number of PFC as the control mice. From these results we conclude that in allogeneic bone marrow chimeras primary antibody response to T-dependent antigen, such as SRBC, is generated when at least the K end of the H-2 complex is compatible between donor and recipient.